Diffuse syphilitic periostitis in a patient living with human immunodeficiency virus: A case report and review of syphilitic periostitis/protean syphilis - Jordan Nathanielsz; Adrian Alexander; Simon Nazaretian; Gail Cross (CMI Communications)
There has been a resurgence of syphilis over the past two decades, with a disproportionate impact on men who have sex with men and people living with human immunodeficiency virus (PLHIV). This case report details a rare manifestation of diffuse syphilitic periostitis in a 40-year-old man living with HIV with a suppressed viral load and a CD4+ T-cell count >500. He developed diffuse multifocal periostitis characterised by severe ostealgia and systemic symptoms. A review of the current English-based literature relating to non-congenital manifestations of syphilis in the bone between 1980 and 2024 identified 40 other cases. Although osteitis was once frequently diagnosed in the setting of congenital syphilis, it is rare in acquired infection, with an estimated incidence of 0.2% per adult case. Of the published cases, 82.5% occurred in males, with a median age of 37.5. HIV co-infection was present in 62.5% of cases, with an average CD4+ T-cell count of 389 per/µL. The calvarium (55%) and the tibia and fibula (52.5%) were the most commonly affected sites, and more than half of the cases (45%) involved multiple bones. In this review we find that CT and MRI have better sensitivity than plain X-rays and describe the utility of bone scintigraphy in identifying diffuse disease. Cases of treatment failure have been reported following intramuscular benzathine penicillin G, where a combination of intravenous treatment followed by intramuscular long-acting benzathine penicillin G may be more effective for disseminated infection.